Externality Analysis of The Existence of The Tahu Tempe Home Industry on The Economy and The Environment of The Surrounding Community (Case Study of Gunung Sulah Tahu and Tempe Industry) - Rosa Indah, Sopiah; Marselina, Marselina (International Journal of Social Science, Education, Communication and Economics, 2023)
This study aims to obtain an overview of the externalities of the tofu home industry in gunung sulah village on the economy and the environment that occurs in the community around the tahu tempe industry. sample and research. data collection techniques used in this research are interviews, questionnaires, observation, and documentation. the results showed that 86% of respondents agreed that the tahu tempe home industry had a good impact on the economy of the gunung sulah village community and 70% agreed that the tahu tempe home industry had a bad impact on the environment around the gunung sulah village community.